Literature Review: Genetic Engineering in Tuberculosis Vaccine Production - Putri, Dhea Rizma Demula; Inggit, Baiq Putri Maharani Bine; Rahmatullah, Lalu Mas’ud; Dalila, Virga Fathiya; Utari, Weny Syafitri; Listyacahyani, Anggit (Jurnal Biologi Tropis, 2024)
The tuberculosis (TB) vaccine contains a weakened form of the TB-causing agent. Currently, much research has focused on developing an effective and safe TB vaccine through genetic engineering. This review aims to analyze genetic engineering techniques in the production of tuberculosis (TB) vaccines. The analysis was conducted by gathering research data from various studies published between 2014-2024, available in PubMed, ScienceDirect, and Google Scholar, using relevant keywords. Based on the literature review, several innovative methods in genetic engineering were identified, such as Polymerase Chain Reaction (PCR), Enzyme-Linked Immunosorbent Assay (ELISA), in silico methods, multi-epitope vaccine development, and protein fusion-based vaccine development. Although there are challenges related to vaccine stability and clinical safety testing, innovations in genetic engineering technology hold the promise of significant progress in developing a more effective and durable TB vaccine. Among these methods, protein fusion-based and multi-epitope vaccines show the most promising potential in terms of effectiveness and long-lasting immune response.